Customer satisfaction is based on Service Quality, Price and Promotion (Case Study On The Gazebo Café Bogor) - Elly Rahmawati; Sudarijati; Yulianingsih (MultiTech Publisher, 2024)
This research aims to determine the simultaneous and partial influence of service quality, price, and promotion on customer satisfaction at The Gazebo Cafe. Questionnaires were distributed to 100 respondents using purposive sampling with the following criteria: customers who have made at least two visits and customers who are considered mature enough to fill out the questionnaire and are at least 17 years old. The questionnaires were tested for validity, reliability, and classical assumption testing. The results of these tests showed that the questionnaires were valid, reliable, and could be used for regression data. The analytical method used in this study was a descriptive and verificative method with a quantitative approach. The results of the study showed that the variables of service quality, price, and promotion, both simultaneously and partially, have a positive and significant effect on customer satisfaction at The Gazebo Cafe. The coefficient of determination (R Square) value is 72,4%. The relationship between service quality, price, and promotion and customer satisfaction is very strong, with a value of 0,851.